Microsoft Windows Vista unveiled - McFedries, Paul (Sams, 2006)
Look beyond the hype-new and noteworthy and what Vista really means for tomorrow's desktop. Covers the Beta 2 release of Windows® Vista An unbiased, unvarnished sneak peek at everything that's new, noteworthy, and ready for prime time in Windows Vista. Microsoft Windows Vista Unveiled is an in-depth exploration of the public release Beta 2 version of Windows Vista, Microsoft's next major operating system and the successor to Windows XP. Whether you're just planning ahead for a future upgrade or running Beta 2 already, Microsoft Windows Vista Unveiled takes you on a detailed tour of all the new and improved technologies, features, tools, and programs that Microsoft programmers have stitched into the Vista fabric. You will learn not only what features are new in Vista, but also why they're important (or not), who they were designed for, and how they will affect your computing life. The goal of this book is to give you an exhaustive sneak preview of Vista's innovations and changes so that by the end of the book you should know whether Vista is for you and what you can expect when you sit down in front of this new operating system. Here's what you'll find inside... In-depth coverage of all the new and improved Windows Vista tools and technologies A tour of the new Windows Vista interface, including Aero Glass What hardware you need to get the most out of Windows Vista Vista's file system improvements, including tags, Quick Search, and virtual folders A review of Vista's new performance and stability features A critical look at the beefed-up security features, including Windows Defender, the new Firewall, and User Account Control A complete look at Vista's totally redesigned networking tools In-depth coverage of Vista's new and improved tools for notebooks and Tablet PCs, digital media, and gaming Paul McFedries is the president of Logophilia Limited, a technical writing company. He has been working with computers for more than 30 years, has been using Microsoft Windows since version 1, and is widely viewed as an expert in explaining Windows and Windows technology. Paul has written more than 40 books that have sold nearly three million copies worldwide, including Microsoft Windows Vista Unleashed, available January 2007.